Posterior Reversible Encephalopathy Syndrome Presenting with Atypical Findings: Report of Two Cases. (25th November 2018) - Cerrone, Paolo; Sucapane, Patrizia; Totaro, Rocco; Sacco, Simona; Carolei, Antonio; Marini, Carmine
Abstract : Background . Posterior reversible encephalopathy syndrome (PRES) is characterized by a variable association of symptoms including headache, consciousness impairment, visual disturbances, seizures, and focal neurological signs. Treating the underlying cause usually leads to partial or complete resolution of symptoms within days or weeks. Brain MRI findings include hyperintensities on T2-weighted sequences and their reversibility on follow-up exams. We describe two patients, one with an atypical clinical presentation characterized by a severe and prolonged impairment of consciousness and the other with atypical neuroimaging findings. Case Presentation . The first patient was a 42-year-old woman, with a negative medical history, presenting with seizures, lethargy, and left hemiparesis, 60 hours after uncomplicated delivery. Brain MRI showed an atypical pattern of alterations, with patchy asymmetric distribution in all lobes. Symptoms completely resolved after twelve days. The second patient was a 59-year-old woman with a history of hypertension, presenting with severe impairment of consciousness, vision loss, and seizures. Symptoms partially resolved after three weeks. Conclusion . PRES is characterized by reversible symptoms and radiological findings. Brain MRI usually shows widespread oedema in white matter with typical patterns. The cases we described suggest that PRES may presents with atypical symptoms and radiological manifestations, mimicking other neurological conditions.